The Chain Mediating Effect of the Public's Online Health Information-Seeking Behavior on Doctor-Patient Interaction - Luo, Aijing; Yu, Zhen; Liu, Fei; Xie, Wenzhao (Frontiers in Public Health, 2022)
Objective This paper aims to explore the influence mechanisms of online health information-seeking behavior (OHISB) on doctor-patient interactions from a psychological perspective, using theory as a guide, which can effectively guide the mode of doctor-patient interaction after search behavior in China. Methods We conducted a convenient web-based survey among members of the public who engage in searching behavior in China using a pretested structured questionnaire. Structural equation modeling was performed for path analysis and mediating effect testing. Results The findings of the study show that (1) 4 control variables (education level, occupation, income, and diagnosed disease) had significant differences in online health information-seeking behavior; 7 control variables (age, gender, living area, education level, occupation, income, medical insurance) were significantly different in doctor-patient interaction behaviors. (2) perceived disease severity (95% CI: 0.003, 0.04, P < 0.001), perceived action benefits (95% CI: 0.059, 0.138, P < 0.001), and e-health literacy (95% CI: 0.061, 0.155, P < 0.001) were positive predictors between OHISB and doctor-patient interactions. (2) E-health literacy and perceived disease severity (95% CI: 0.001, 0.013, P < 0.05), and e-health literacy and perceived action benefits (95% CI: 0.082, 0.166, P < 0.001) play chain mediating roles between OHISB and doctor-patient interactions. Conclusions E-health literacy, perceived disease severity, and perceived action benefits act as chain mediators between OHISB and doctor-patient interactions.